The relational responding task: toward a new implicit measure of beliefs - De Houwer, Jan; Heider, Niclas; Spruyt, Adriaan; Roets, Arne; Hughes, Sean (Frontiers in Psychology, 2015)
We introduce the Relational Responding Task (RRT) as a tool for capturing beliefs at the implicit level. Flemish participants were asked to respond as if they believed that Flemish people are more intelligent than immigrants (e.g., respond “true” to the statement “Flemish people are wiser than immigrants”) or to respond as if they believed that immigrants are more intelligent than Flemish people (e.g., respond “true” to the statement “Flemish people are dumber than immigrants”). The difference in performance between these two tasks correlated with ratings of the extent to which participants explicitly endorsed the belief that Flemish people are more intelligent than immigrants and with questionnaire measures of subtle and blatant racism. The current study provides a first step towards validating RRT effects as a viable measure of implicit beliefs.